VALUE DIMENSIONS OF QUALITY CULTURE IN HIGHER EDUCATION - Маслікова, Ірина (Ukrainian Cultural Studies, 2023)
The article analyses the changes in the social and cultural context in the functioning of the modern university, which lead to the actualization of the issues of development of quality culture and its assurance. It is identified that the problems of quality assessment arise due to the insufficient articulation of the essence of concept of "quality" and "quality culture" in international standards and national legislation. The purpose of the study is to define the essence and dimensions of quality culture as a necessary element of the mission of a contemporary university. Results. It is noted that in current processes of quality assurance in the higher education and its assessment there is an excessive focus on purely managerial procedures, which results in threats to the cultural mission of the contemporary university and loss of motivation for authentical academic activity. Consideration of complex educational activities through the prism of the quality of learning outcomes and the quality of research, teaching, learning, and assessment processes opens up prospects for theoretical justification of quality requirements with the use of the theories of consequentialism and virtue ethics. The article demonstrates the possibilities of justification the quality in education from the standpoint of the common good of all stakeholders, firstly, as maximizing the instrumental goods of all participants in the educational process and, secondly, as continuous improvement of members of the university community in complex joint activities based on "intrinsic" values. Thus, the university is able to realize its mission, which can combine instrumental "extrinsic" and self-sufficient "intrinsic" values-goals. In this way the understood quality in education allows to broaden the focus of consideration of the essence of quality culture, which is unique for each university. Quality culture, as an element of organizational culture, bears the imprint of the value system of national culture, the value system of the professional activity for which the university prepares future specialists, the value system of subcultures that arise within the university (academic groups, departments, faculties; teachers, students, administration, etc.) Given the multidirectional incorporation of members of the university community into the system of social relations, it is proposed to consider the culture of quality through the prism of four structural elements - value, normative, sign and symbolic, and managerial components. Taking into account the fact the non-homogeneous nature of the quality culture of each university, its assessment remains problematic both by the university itself and by institutions of external evaluation.
Keywords: quality in education; quality culture in high education; cultural mission of the university; "intrinsic" values of educational activity; instrumental goals of the university